Factors associated with responses to potential rejection by specific others - Jones, Tucker L. (Kansas State University, 2018)
The present study is an extension of our prior work (Jones et al., 2016) and explored two specific goals. The primary goal examined the predictive ability of target-specific, rejection-relevant individual difference measures on participants’ anticipated emotional and behavioral responses to ambiguous social situations involving specific potential rejectors (i.e., significant others, friends, acquaintances). The secondary goal explored differences in participants’ anticipated emotional and behavioral responses to perceived rejection by the same potential rejectors. Concerning the primary goal, correlations revealed that previous experience with and/or sensitivity to being rejected by any individual is associated with heightened anticipated emotional responses which, in turn, is associated with different anticipated behavioral responses. However, path analyses revealed that the target-specific, rejection-relevant individual difference variables used in the current study were uniquely predictive of participants’ anticipated responses to ambiguous social situations involving similar potential rejectors, but only for those who read about potentially being rejected by a friend (results of the path analyses for those who read about potential rejection by significant others or acquaintances were uninterpretable). Concerning the secondary goal, analyses revealed that the intensity of the emotional responses as well as the type of behavioral response were dependent on the role of the potential rejector. Taken together, the present findings provide insight into the individual differences associated with our tendency to feel and behave as if we have been rejected within ambiguous social situations and help to shed additional light on the dyadic nature of interpersonal rejection.
Keywords: Rejection; Ambiguity; Individual differences; Emotional responses; Behavioral responses